محمد إقبال والقلق الصوفي: Sufi Muhammad Iqbal and Anxiety - الخوالدة, سميرة (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2016)
تتناول هذه الدراسة بالتحليل موقف إقبال من الفكر والتراث الصوفي؛ وتلقي الضوء على المؤثرات التي ساهمت في تشكيل هذا الموقف والتطورات التي مر بها، ويمكن تحديدها بثلاث مراحل؛ الأولى: من البدايات وحتى عودته من دراسته في أوروبا، وهي مرحلة أعجب فيها بشعراء الصوفية ومعظمهم قد كتب بالفارسية. وفيها يظهر تأثير المستشرقين الذين درس معهم في تلك الفترة. والمرحلة الثانية: تمثل ظهور الوعي المستقل لديه، فتتحول نظرته من الإعجاب الطاغي إلى إعجاب ناقد انتقائي، ويتشكل لديه وعي بواقع العالم الإسلامي وبالعلاقات الحقيقية بين الشرق والغرب المبنية على التفوق والاستعمار. أما المرحلة الثالثة؛ فتتمثل في كتابه "تجديد الفكر الديني في الإسلام"، ففيها قدم إقبال فلسفته في إعادة البناء الروحي البديل لصوفية الماضي، مؤكداً أن عملية إعادة البناء الروحي هذه المستمدة من القرآن والسنة النبوية هي علاج التخلف في المجتمعات المسلمة، وسبيل استعادة مجدها في الحاضر. The purpose of this study is to investigate Muhammad Iqbal's position on Sufi thought and heritage, and to illuminate the factors that have helped to shape this position and its development. Three phases can be discerned: the first extends from the beginning to his return from Europe, in which he admired Persian Sufi poets, and showed some influence of Orientalist scholars on him. The second demonstrates independence of thought, where admiration is disciplined by the adoption of a selective, critical approach, where he built an awareness of the true nature of the relations between the East and the West, founded on West supremacy and colonialism. In the third phase Iqbal presents his own reformative conception of spiritual reconstruction derived from the Holy Qur'an and Prophetic Tradition.